ChemInform Abstract: Regenerative Glycosylation under Nucleophilic Catalysis. Issue 32 (24th July 2014) - Nigudkar, Swati S.; Stine, Keith J.; Demchenko, Alexei V.
Abstract: Glycosylation in the presence of difluorooxindole proceeds in a regenerative manner, allowing to use only catalytic amounts of this activator.